Vehicle equipment selection model for preliminary design using fuzzy multi-criteria decision making method - Abd. Kader, Ab. Saman; Idris, Jamaliah; Abdul Mukti, Mohd. Afifi; Ahmad, Mohd. Zamani (2006)
Equipments selection process is one of the key planning and design activities of marine, land and air vehicles. Equipments are often selected from a set of possible alternatives. More than one decision makers are usually involved and selection of one particular choice is made against a set of strategic selection criteria. Approximate mode of decisionmaking is normally employed and hence selection criteria are subjectively specified. This paper presents the fuzzy approach to the subjective representation of design data and the multi-criteria decision making method to the treatment of subjective criteria rating and ranking of equipment to serve as collective decision making tool